STUDY OF ENDOMETRIAL PATHOLOGY IN ABNORMAL UTERINE BLEEDING - DUBEY, ANJALI; SHRIVASTAVA, PRATISHTHA; JAIN, KONIKA (International Journal of Current Pharmaceutical Research, 2024)
Objective: Endometrial pathology is becoming the most common issue that affects women of reproductive age group worldwide. AUB encompasses a wide variety of presentations, for example, frequent menstrual cycles, frequent and heavy cyclical bleeding, irregular bleeding, and postcoital bleeding. This study was done to evaluate the endometrial causes of AUB and to determine the specific pathology in different age groups. Methods: This study was a prospective cross-sectional study conducted on 200 patients from January 2023 to October 2023 in the department of pathology in a reputed teaching hospital and research centre. All the endometrial biopsies/curretages and hysterectomy specimens sent for Histopathological examination with history of AUB were included in the study. Results: Age of the patients with AUB ranged from 17 to 71 y in our study. Out of 200 cases, 90 cases (45%) were seen in Perimenopausal group followed by 68 cases (34 %) in Reproductive age group and 42 cases (21%) in Postmenopausal age group. Menorrhagia was the most common bleeding pattern seen in 54% pf patient with AUB. In 28% in reproductive age group, hormonal imbalance was observed in 13% of reproductive age group and 6% in perimenopausal age group. Atrophic endometrium was observed in 7.5% of women in post-menopausal age group. Chronic endometritis was seen 3% of reproductive age group. Conclusion: Abnormal uterine bleeding in women belonging to different age group show variable endometrial pattern on histopathological examination. They are valuable in early detection of pre-cancerous endometrial lesions as well as malignancy.